Pengembangan ide inovasi mochi berisi brownies dengan menggunakan proses design thinking - Gracia, Nicole; Wijayanto Aripradono, Heru (Jurnal Paradigma Ekonomika, 2024)
The dessert industry faces the ongoing challenge of innovation, where existing products often share similarities in taste and presentation. This study aims to develop an innovative dessert product by combining mochi and brownies, using the Design Thinking approach. The approach involves five main stages: Empathize, Define, Ideate, Prototype, and Test. The process begins with observation and interviews to understand consumer needs and preferences. Based on initial findings, creative ideas were developed to create a unique dessert product, Mochi Brownies or "Mownies," combining the chewy texture of mochi with the softness of brownies. The product prototype was tested to evaluate taste, texture, and packaging design, with consumer feedback used to refine the product. The findings indicate that the use of Design Thinking is effective in creating a product that meets consumer needs and provides a new culinary experience. This study recommends continuous product development, enhanced packaging quality and design, as well as the application of effective marketing strategies to improve the product’s competitiveness in the market.